2019
DOI: 10.3390/su11133607
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Sustainable Food Market Generation Z Consumer Segments

Abstract: This study explores the interaction between environmental consciousness and sustainable food attributes as predictors in the market segmentation process for sustainable foods with respect to United States (U.S.) Generation Z (Gen Z) consumers. This study was executed using a cross-national, web-based survey to analyze and categorize Gen Z female (n = 435) and male (n = 377) consumers between 18 and 23 years of age living in the continental United States. The objectives of this study were to classify U.S. Gen Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(194 citation statements)
references
References 38 publications
7
137
0
Order By: Relevance
“…Su et al [114] Z Segmentation based on environmental consciousness and sustainable food attributes USA, N = 812 High, moderate, and low environmentally conscious groups were found. The first two groups considered health and environmental elements when purchasing sustainable food, and the third group considered elements such as price and convenience…”
Section: Leerattanakorn Et Al [104] Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Su et al [114] Z Segmentation based on environmental consciousness and sustainable food attributes USA, N = 812 High, moderate, and low environmentally conscious groups were found. The first two groups considered health and environmental elements when purchasing sustainable food, and the third group considered elements such as price and convenience…”
Section: Leerattanakorn Et Al [104] Ymentioning
confidence: 99%
“…Studies that have focused on or include generational cohorts and SFC, and/or organic food products in general or specifically, are limited (to our knowledge), and they emphasize on one generation, with a particular tendency to Gen Y/Millennials [11,34,57,[102][103][104][105][106][107][108][109][110][111][112][113][114]. Table 1 presents the studies that-to the author's knowledge-focus on SFC or OFB combined with generational cohorts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the green context, several studies have examined the moderating role of age but have produced inconsistent findings: While some studies suggest that green consumers tend to be older-aged who are more ecologically conscious and have a greater tendency to purchase green products/services [40][41][42][43], others indicated that younger consumers tend to be more concerned about the environment and are known to actively adopt green products based on their intrinsic proenvironmental values [44,45]. In the green hotels context, authors in [41,42] have found that older tourists have stronger intentions to adopt proenvironmental behaviors, as well as to pay more for visiting the hotel.…”
Section: Generational Cohortmentioning
confidence: 99%
“…Moreover, another moderating variable is consumers' age, which is considered as a strong criterion to explain differences in environmental context [40]. Several studies in the green tourism context have examined the moderating role of age but have produced different findings: While some studies suggested that older tourists have stronger intentions to adopt proenvironmental behaviors [40][41][42][43], others indicated that younger tourists tend to be more concerned about the environment [44,45]. Thus, we aim to analyze the moderating role of the guests' age in the causal relationships between the aforementioned constructs in four generational cohorts (Gen Z, Gen Y, Gen X, and Baby Boomers).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these generations is unique, liking and disliking, preferences, and work orientations (Betz, 2019). Su, Tsai, Chen, and Lv (2019) stated that the Gen Z population constituted 32% of the 7.7 billion global population in 2019. WHO (2017) report stated that the elderly population is increasing worldwide both in developed and developing countries. By 2050, the proportion of the elderly population globally is expected to increase to 22% (an estimated two billion older people) (Geyer & Louw, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%